2016
DOI: 10.1016/j.ecoleng.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

A microbial fuel cell-coupled constructed wetland promotes degradation of azo dye decolorization products

Abstract: a b s t r a c tMicrobial fuel cell coupled constructed wetland (CW-MFC) was constructed for azo dye decolorization and further degradation. Methyl Orange (MO) was chosen as the model azo dye due to the simple decolorization products. The decolorization products were analyzed qualitatively via GC-MS and the N,NDimethyl-p-phenylenediamine (DMPD) was chosen as one of the MO decolorization products to study the further degradation performance of decolorization products in the CW-MFC. 1,4-Benzenediamine, N-methyl-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The 20-cm and 20-cm-p CW-MFCs had negative ABRX3 decolorization volumes in the cathode layer, similar to observations in our previous study (Fang et al, 2016). This may have occurred because of evaporation in the cathode layer.…”
Section: Figure 5 Is Heresupporting
confidence: 82%
See 2 more Smart Citations
“…The 20-cm and 20-cm-p CW-MFCs had negative ABRX3 decolorization volumes in the cathode layer, similar to observations in our previous study (Fang et al, 2016). This may have occurred because of evaporation in the cathode layer.…”
Section: Figure 5 Is Heresupporting
confidence: 82%
“…Therefore a part of treatment that happened in CW-MFCs was caused because bioelectrochemical. In our previous researches, we have setted control experiment that without circuit, the experimental results showed the circuit can improve the degradation of azo dyes (Fang et al, 2013;Fang et al, 2016). At low ABRX3 concentrations, the system did not require many electrons for ABRX3 decolorization or electricity generation.…”
Section: Abrx3 Decolorization and Chemical Oxygen Demand Removalmentioning
confidence: 95%
See 1 more Smart Citation
“…Most researchers used glucose and sucrose as carbon source and model pollutants. However, there are limited studies on sodium benzoate [13,19,20]. Therefore, the authors chose sodium benzoate as model pollutant in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Shewanella oneidensis MR-1 has been proposed to follow the reverse Mtr pathway of electron transfer for reductive metabolism ( Ross et al., 2011 ) and electron uptake from the cathode electrode ( Rowe et al., 2018 ). Several studies have reported on the electrotrophic mixed-culture microbial biofilms, grown with electron acceptors such as oxygen ( Rabaey et al., 2008 ), H + ions ( Aulenta et al., 2008 ), CO 2 ( Aryal et al., 2017 ), heavy metals, polyaromatic hydrocarbons, dyes, and so on ( Gregory and Lovley, 2005 ; Tandukar et al., 2009 ; Sharma et al., 2020 ; Fang et al., 2016 ). Notably, EAMs have been studied mostly from nonextreme environments, and only a few studies have reported the diversity of these microbes inhabiting extreme habitats ( Koch and Harnisch, 2016 ; Rowe et al., 2017 ; Logan et al., 2019 ; Yadav and Patil, 2020 ).…”
Section: Introductionmentioning
confidence: 99%